2014
DOI: 10.1371/journal.pone.0091846
|View full text |Cite
|
Sign up to set email alerts
|

How Is Emotional Awareness Related to Emotion Regulation Strategies and Self-Reported Negative Affect in the General Population?

Abstract: ObjectiveThe Levels of Emotional Awareness Scale (LEAS) as a performance task discriminates between implicit or subconscious and explicit or conscious levels of emotional awareness. An impaired awareness of one's feeling states may influence emotion regulation strategies and self-reports of negative emotions. To determine this influence, we applied the LEAS and self-report measures for emotion regulation strategies and negative affect in a representative sample of the German general population.Sample and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 36 publications
6
60
1
1
Order By: Relevance
“…Therefore, higher levels of attention to emotions and clarity of emotions are expected to aid adaptive emotion regulation strategies by providing more accurate emotional data. Support for this explanation includes findings from a recent study by Subic-Wrana et al (2014), which suggested that higher levels of emotional awareness were a precondition to using reappraisal-an adaptive emotion regulation strategy-effectively. With regard to the present study, it is possible that having higher levels of emotional awareness contributes to more adaptive emotion regulation, which counteracts the deleterious effect of urgency, and in turn leads to diminished binge eating outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, higher levels of attention to emotions and clarity of emotions are expected to aid adaptive emotion regulation strategies by providing more accurate emotional data. Support for this explanation includes findings from a recent study by Subic-Wrana et al (2014), which suggested that higher levels of emotional awareness were a precondition to using reappraisal-an adaptive emotion regulation strategy-effectively. With regard to the present study, it is possible that having higher levels of emotional awareness contributes to more adaptive emotion regulation, which counteracts the deleterious effect of urgency, and in turn leads to diminished binge eating outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Limited research attempted to explore some aspect of this relationship, whereas there are virtually no empirical data on when or why relations exist (or do not exist). In one of these works, Subic-Wrana et al (2014) examines the way emotion awareness influences emotion regulation strategies and self-reports of negative emotions. Their first findings suggested that conscious awareness of emotions may be a precondition for the use of reappraisal as an adaptive emotion regulation strategy.…”
Section: Emotion Awarenessmentioning
confidence: 99%
“…Valid emotion identification is considered a precursor for adaptive emotion regulation (Subic-Wrana et al, 2014). Functional magnetic resonance imagery studies have associated emotion identification with a subsequent decrease in amygdala activity (Lieberman et al, 2007), which indicates that labeling an emotion might be a form of arousal regulation itself.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion identification is defined as the ability to identify and label a specific self-experienced emotion, and is a key feature to adaptive emotion regulation and interpersonal communication of feelings (Lane and Schwartz, 1987; Subic-Wrana et al, 2014). Most research on emotion identification in eating disorders has relied on questionnaires regarding alexithymia, a broader personality-based concept characterized by a reduced ability to identify, differentiate and communicate emotions (Nowakowski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%